The role of human rights litigation in improving access to reproductive health care and achieving reductions in maternal mortality - Jennifer Templeton Dunn; Katherine Lesyna; Anna Zaret (BMC, 2017)
Abstract Background Improving maternal health, reducing global maternal mortality, and working toward universal access to reproductive health care are global priorities for United Nations agencies, national governments, and civil society organizations. Human rights lawyers have joined this global movement, using international law and domestic constitutions to hold nations accountable for preventable maternal death and for failing to provide access to reproductive health care services. Case presentation This article discusses three decisions in which international treaty bodies find the nations of Brazil and Peru responsible for violations of the Convention on the Elimination of All Forms of Discrimination Against Women and the International Covenant on Civil and Political Rights and also two domestic decisions alleging constitutional violations in India and Uganda. Conclusions The authors analyze the impact of these decisions on access to maternal and other reproductive health services in Brazil, Peru, India, and Uganda and conclude that litigation is most effective when aligned with ongoing efforts by the public health community and civil society organizations. In filing these complaints and cases on behalf of individual women and their families, legal advocates highlight health system failures and challenge the historical structures and hierarchies that discriminate against and devalue women. These international and domestic decisions empower women and their communities and inspire nations and other stakeholders to commit to broader social, economic, and political change. Human rights litigation brings attention to existing public health campaigns and supports the development of local and global movements and coalitions to improve women's health.